1973
DOI: 10.1071/bt9730053
|View full text |Cite
|
Sign up to set email alerts
|

Die-Back Tolerance in Eucalypt Species in Relation to Fertilization and Soil Populations of Phytophthora cinnamomi

Abstract: The die-back tolerance of 16 fertilized (17/9/7 nitrogen-phosphorus-potassium) and unfertilized eucalypt and two conifer species was tested in the coastal forests of east Gippsland on sites rated as of "high", "moderate", and "low" hazard on the basis of previous damage, internal soil drainage, and infection by P. cinnamomi. Measurements were made of the population density index (PDI) of P. cinnamomi, of soil moisture, and of soil temperature. Supporting greenhouse and laboratory experiments are also reported.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…These changes inhibit mycorrhizae, stimulate unfavourable microbes in the soil (e.g. Marks et al, 1973Marks et al, , 1975Ellis and Pennington, 1992;Florence, 1996;Davison, 1997;Shearer and Smith, 2000) and make the sap and leaves of trees more nutritious, palatable and accessible to pests, parasites and pathogens (e.g. Landsberg et al, 1990;Granger et al, 1994;Turner, 2004).…”
Section: Fire Grazing and Eucalypt Declinementioning
confidence: 97%
“…These changes inhibit mycorrhizae, stimulate unfavourable microbes in the soil (e.g. Marks et al, 1973Marks et al, , 1975Ellis and Pennington, 1992;Florence, 1996;Davison, 1997;Shearer and Smith, 2000) and make the sap and leaves of trees more nutritious, palatable and accessible to pests, parasites and pathogens (e.g. Landsberg et al, 1990;Granger et al, 1994;Turner, 2004).…”
Section: Fire Grazing and Eucalypt Declinementioning
confidence: 97%
“…Some site environmental conditions could potentially influence the lesion areas in the particular genotypes used in the test. For instance, the elevated concentrations of nitrogen have frequently been reported as a factor potentially increasing Phytophthora disease severity in trees (Marks et al 1973;Utkhede and Smith 1995;Scarlett et al 2013). Gibbs et al (1999) found a correlation between concentrations of nitrate nitrogen in river water and the severity of disease in riparian alder stands in England, although this relationship was not studied in detail and was not confirmed in latter study in France (Thoirain et al 2007).…”
Section: Discussionmentioning
confidence: 90%
“…For instance, the elevated concentrations of nitrogen have frequently been reported as a factor potentially increasing Phytophthora disease severity in trees (Marks et al. ; Utkhede and Smith ; Scarlett et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…The direct influence of soil chemical factors on development of P. cinnamomi has been studied less than soil physical factors. Fertilising P. cinnamomi conducive sites with NPK fertiliser increased mortality of susceptible Eucalypts (Marks et al 1973). This response is contrary to disease expression in suppressive sites which have higher levels of N,P and K relative to conducive sites but slower rates of disease development.…”
Section: Discussionmentioning
confidence: 97%